Faecalibacterium prausnitzii-derived extracellular vesicles alleviate chronic colitis-related intestinal fibrosis by macrophage metabolic reprogramming - Ying Wang; Linjie Li; Shuze Chen; Zonglin Yu; Xuefeng Gao; Xiaojie Peng; Qiujuan Ye; Zitong Li; Weihao Tan; Ye Chen (Elsevier, 2024)
Faecalibacterium prausnitzii (F. prausnitzii) has been recognized for its various intestinal and extraintestinal benefits to human. And reduction of F. prausnitzii has been linked to an increased risk of intestinal fibrosis in patients of Crohn's disease (CD). In this study, oral administration of either live F. prausnitzii or its extracellular vesicles (FEVs) can markedly mitigate the severity of fibrosis in mice induced by repetitive administration of DSS. In vitro experiment revealed that FEVs were capable of directing the polarization of peripheral blood mononuclear cells (PBMCs) towards an M2b macrophage phenotype, which has been associated with anti-fibrotic activities. This effect of FEV was found to be stable under various conditions that promote the development of pro-fibrotic M1/M2a/M2c macrophages. Proteomics and RNA sequencing were performed to uncover the molecular modulation of macrophages by FEVs. Notably, we found that FEVs reprogramed every metabolism of macrophages by damaging the mitochondria, and inhibited oxidative phosphorylation and glycolysis. Moreover, FEV-treated macrophages showed a decreased expression of PPARγ and an altered lipid processing phenotype characterized by decreased cholesterol efflux, which may promote energy reprogramming. Taken together, these findings identify FEV as a driver of macrophage reprogramming, suggesting that triggering M2b macrophage polarization by oral admiration of FEV may serve as strategy to alleviate hyperfibrotic intestine conditions in CD.